Doing Special Things to Special People in Special Places: Psychologists in the CIA Torture Program - Welch, Michael (The prison journal, 2017)
Since 2014, detailed correspondence between the American Psychological Association (APA) and the Central Intelligence Agency (CIA) reveal the extent to which operational psychologists coordinated with the Bush administration’s enhanced interrogation program. Key revelations expose the ethical maneuvering intended to defend the participation of certain psychologists in interrogation, abuse, and torture, including waterboarding. This critique takes aim at the controversy over the psychological planning and subsequent practice of torture during the Bush administration. Analysis is informed by Robert Jay Lifton and his book The Nazi Doctors: Medical Killing and the Psychology of Genocide.